(untitled) (Journal of International Studies, 2020)
Today, bidding to host international sports events is no longer a privilege of certain developed countries. Hosting international sports events has attracted many developing countries, as they have begun to realize the multiple benefits that it can offer. Sports as a form of popular culture that cuts across class, caste and ethnicity has a lot to offer to many developing countries that are still grappling with many crucial national agendas, provided its benefits and potential effects are creatively exploited. The successful hosting of a high-profile international sports event would not only trigger and promote national pride and a sense of patriotism, but quite often, its socio-economic outcome may outweigh the political effects. Whilst the political focus of sports is usually related to aspects such as national pride, improving the image of a nation as well as national unity, the economic dimension of sports has always been linked to economic growth, tourism and creating new frontiers for the economy. Over the past decade Malaysia has seen growing interest and intensive government investment in sports. The success of the Kuala Lumpur 1998 Commonwealth Games and the Sepang Formula 1 Grand Prix has gained the country outstanding international reputation in the hosting of world sports events, despite its average achievements in sports. This paper attempts to examine the underlying factors that prompted Malaysia to actively become involved in promoting itself as a host country for several world sports events in which it has never before partaken nor had achieved international reputation. In addition it will also look into the country sports policy as well as the roles of government and sports bodies in making sports an important dimension to strengthen the country’s domestic and international agendas. The paper argues that for many developing countries, the role of government is still far more crucial than any other factors in the development of sports. Sports havefar-reaching implications in the development of a country and should not be viewedmerely as a form of popular culture. Therefore, many more ’focus studies’ should becarried out to further apprehend the contribution that sports could make in developingcountries.